Evaluation of Degree of Consolidation, Over Consolidation Ratio and Coefficient of Consolidation from CPTu tests in Alluvium Clays - Lie, Edwin; Lim, Aswin (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2023)
Soft soil was found in several areas in Indonesia, one of them is in Kalimantan Island, which the soft soil in the island mostly formed by Alluvium.  One of the characteristics of the soft soil is that they are likely still in under consolidating stage. The usage of CPTu was found to be suitable to the soft soil as the device can record small numbers continuously and able to record pore water pressure. Key features in performing CPTu in under consolidating soft soil is the dissipation test. However, often the dissipation test ended before the 50% excess pore pressure dissipated, which causes commonly used method for interpretation unable to estimate u50. Inverse time (Whittle et. al., 2000; Lim et. al., 2014) and inverse square root time (Liu et. al., 2014) method was developed to overcame the limitation. Rahardjo et. al. (2016) also developed method for obtaining degree of consolidation (and OCR) using pore pressure ratio parameter (Bq) obtained from CPTu.  Geotechnical investigation comprised advancing several cone penetration testings (CPTu) were carried out after failure occurred in a relatively flat area (RL +5m to +12m) after having built waste dump embankment to +70m elevation. Soft soil with 15m to 30m thickness was found beneath the embankment. This paper presents comparison of coefficient of consolidation using Teh & Houlsby (1991) method using parameters derived from inverse time and inverse square root time, also comparison for degree of consolidation and OCR in the Alluvium clays based on the dissipation data obtained from the testings.  Result showed that the Alluvium clays in the upper 10m already over consolidated while between RL 0 to -20m are still under consolidating, with parameters obtained using inverse time and inverse square root time generally showing close value.